The Urgency Mechanism of Industrial Relation’s Settlement to Support the Business Climate that Equitable for Workers - Agisa Tri Handias; Muhamad Azhar (Jurnal Hukum Prasada, 2020)
Indonesia has been developed in economical sector, especially in the employment section. Along with the times, there has occur and grown up and many problems about employment matter in which there many more employment relationship works without parity between the responsibility and the rights from the employer to the employee/ workers. As the consequence of the inclusion of business competition climate, it caused the businessman look for ways how to maximize the production output by reducing the costs. This circumstance has influenced the workers right becomes ruled out and then arises statement of workers to claim their pending rights. This study aims to find out the industrial relationship matter related to the business competition climate, and to find out the settlement mechanism of industrial relationship conflict based on regulation number 2 year of 2004 about settlement of industrial relationship matter. This study used juridical normative method. This juridical research is carried out towards references object. Moreover, this study applied primary, secondary, and tertiary legal material. The result of the study showed that the impact of employment matter was more complicated. That is why the labor problems should be seen as the industrial relation matter. This matter also comes as the consequence of Indonesia as the Welfare State where the State should take a part in every part of social life. This means that the State has important role to solve the problem of industrial relationship.